Le fratture della caviglia e del piede in età evolutiva - Samaila, E.M.; Paroni, C.; Vacchiano, A.; Magnan, B. (Lo Scalpello - Journal, 2018)
FOOT AND ANKLE FRACTURESFoot and ankle fractures represent 12% of all paediatric fractures. Physeal growth makes the paediatric patient’s bonedifferent compared to that adults in term of diagnosis, treatment and complications. The diagnosis is based on clinicalexamination and conventional X-ray; CT scans are the gold standard for complex lesions. The most frequentcomplication of physeals injuries is the early closure of the growth plate with possible angular deformities and leglength discrepancy. Most injuries may be treated conservatively. Surgical treatment is necessary when anatomicalreduction cannot be achieved.